Temporal and Spatial Trends of Northern Bobwhite Survival and Nest Success - Chad J. Parent; Fidel Hernandez; David B. Wester; Fred C. Bryant (National Quail Symposium Proceedings, 2017)
The northern bobwhite (Colinus virginianus) has been declining in abundance across North America for many years. It is unknown, however, if other population variables also exhibit this downward trajectory. We conducted a retrospective-analysis of annual survival and nest success based on a literature review of 64 studies and compared these estimates temporally and spatially. We hypothesized that increased management efforts influenced bobwhite survival in the 1990s. Evidence from linear splining indicated survival trends changed in 1994. Thus, we compared trends across 3 periods: before 1994, after 1994, and overall. Mean (6 SD) annual survival was 13.9 6 9.4% across 31 studies from 1970 to 2007. Annual survival decreased 0.534% per year during 1970–1994 and stabilized thereafter. This stabilization in survival occurred along latitudinal and longitudinal gradients in which survival decreased at the northern and western periphery of the bobwhite range. Our linear splining models did not support the hypothesis that trends in nest success changed in the 1990s; thus, we only compared trends across the overall, 1924–2008 range of studies. Mean nest success across 33 studies was 44.4 6 15.2% during this interval and increased slightly across the 1924–2008 range of studies. We observed latitudinal gradients in nest success. Nest success was lowest at the northern periphery of the bobwhite range; it decreased 0.90% per degree of latitude. Annual survival stabilized after 1994 despite monotonic declines in bobwhite abundance since at least the 1960s. Range-wide survival and nest success trends may not parallel trends in abundance, particularly after 1990, which suggests biologists may not fully understand the range-wide population ecology of bobwhites. This lends support for the need to monitor other aspects of the bobwhites range-wide population dynamics as supplements to range-wide abundance.
Keywords: abundance; Colinus virginianus. habitat management; meta-analysis; nest success; northern bobwhite